Electromagnetic illusion with isotropic and homogeneous materials through scattering manipulation. (22nd September 2015) - Yang, Fan; Mei, Zhong Lei; Jiang, Wei Xiang; Cui, Tie Jun
Abstract: A new isotropic and homogeneous illusion device for electromagnetic waves is proposed. This single-shelled device can change the fingerprint of the covered object into another one by manipulating the scattering of the composite structure. We show that an electrically small sphere can be disguised as another small one with different electromagnetic parameters. The device can even make a dielectric sphere (electrically small) behave like a conducting one. Full-wave simulations confirm the performance of proposed illusion device.